Choroid plexus and pituitary gland hemochromatosis induced by transfusional iron overload: Two case reports - Hiroyuki Fujii, MD, PhD; Mitsuru Matsuki, MD, PhD; Takefumi Hamakawa, MD; Yumiko Toda, MD; Nana Fujii, MD; Sota Masuoka, MD; Akihiro Nakamata, MD; Emiko Chiba, MD, PhD; Kazunari Ishii, MD, PhD; Harushi Mori, MD, PhD (Radiology Case Reports, 2024)
Hemochromatosis is a primary or secondary pathological condition characterized by the deposition of excess iron in the body tissues, which can eventually lead to cellular damage and organ dysfunction. Although excess iron deposition in the central nervous system is rare, involvement of the choroid plexus, pituitary gland, cortical surfaces, and basal ganglia has been reported to date. This case report describes 2 cases of transfusion-induced hemochromatosis involving the choroid plexus and pituitary gland, which were diagnosed by magnetic resonance imaging (MRI). In both cases, gradient echo (GRE) sequences, such as T2 star-weighted image and susceptibility-weighted imaging demonstrated markedly low signal intensity in the choroid plexus. Furthermore, the pituitary gland showed low signal intensity on T2-weighted images in Patient 2. Because these low signal intensities were not seen prior to red blood cell transfusion, they were diagnosed with transfusion-induced hemochromatosis. Brain MRI with GRE sequences was useful in detecting iron deposition in the choroid plexus. Considering that iron deposition in the body tissues can lead to irreversible organ damage, MRI with GRE sequences should be considered for patients with suspected iron overload.